Зіставний аналіз мовно-змістових деформацій в українському та російському перекладах роману Дж. Р. Р. Толкіна «The Lord of the Rings» за авторством А. Немирової - Кушнір, Лілія Олегівна; Kushnir, L. O. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті зіставлено український і російський переклади першого тому роману Дж. Р. Р. Толкіна «The Lord of the Rings» за авторством А. Немирової. Аналіз якісного складу та кількісних масштабів мовно-змістових перекладацьких деформацій засвідчив, що українському перекладу властиві деякі ознаки вторинності. Наслідками є нагромадження семантичних і стилістичних відхилень від тексту оригіналу на лексичному та фразеологічному рівнях і надмір перекладацьких деформацій в українському перекладі. The article deals with contrastive analysis of the Ukrainian and Russian translations by A. Nemirova of the first volume of the J. R. R. Tolkien’s novel «The Lord of the Rings». The analysis has resulted in obtaining the quantitative data concerned with the structure and the scope of language- and meaning-related translation deformations in the both translations. Issuing from the main features of the translation deformations, the conclusion has been drawn that the Ukrainian translation shows some features revealing its secondary character. The appropriate negative consequences are gradual accumulation of semantic and stylistic deviations from the original text of the novel on the lexical and phraseological levels, as well as a more limited scope of creative translator’s work. An excess of the language-related translation deformations found in the Ukrainian translation is a compulsory result of the practice of secondary translation partly applied by A. Nemirova.
Сontrastive Analysis of Language and Meaning Deformations in the Ukrainian and Russian Translations by A. Nemirova of J. R. R. Tolkien’s Novel «The Lord of the Rings»
Keywords: художній переклад; literary translations; фентезі; fantasy; Дж. Р. Р. Толкін; Tolkien